The Balance of Power: Equal Representation of Member States in EU Institutions - Sándor, Lénárd; Trócsányi, László (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
The principle of (sovereign) equality has been one of the most important building blocks of modern public international law and it has also been one of the founding principles of European integration. While the Founding Treaties include this principle, Member States remain different in many respects in terms of their size, population and economic output, but also in terms of historical experiences, cultural heritage or constitutional identity. In light of this controversy, the present chapter investigates the different aspects of the ‘principle of equality’ and the dilemma it has been posing throughout the evolution of the integration as well as in its institutional arrangement and before its law. In the course of this study, the Chapter aims to shed light on questions such as European democracy and the principle of equality as well as on its relation to the primacy of European law or its process of ‘constitutionalisation’.